IgG4-Related Cholangitis - Beuers, Ulrich; Trampert, David C. (Seminars in Liver Disease, 2025)
IgG4-related cholangitis (IRC) is a rare fibroinflammatory disease of the biliary tree and liver and presents the major hepatobiliary manifestation of IgG4-related systemic disease (IgG4-RD). IRC also includes the IgG4-related inflammatory pseudotumor of the liver and IgG4-related cholecystitis. IRC mimics other cholangiopathies such as primary sclerosing cholangitis or cholangiocarcinoma. IRC may be found in 30 to 60% of cases with type 1 autoimmune pancreatitis, the most frequent manifestation of IgG4-RD. The pathogenesis of IRC (and IgG4-RD) is incompletely understood. Genetic predisposition, environmental factors, oligoclonal glucocorticosteroid-sensitive expansion of IgG4+ B cells/plasmablasts in blood and affected tissue and blocking autoantibody formation against protective IgG4-specific autoantigens such as annexin A11 and laminin 511-E8 with impaired protection of biliary epithelia against toxic bile acids have been described in IRC. Specific T cell subtypes are involved in the inflammatory process. The diagnosis of IRC is made according to HISORt criteria comprising histopathology, imaging, serology, other organ manifestations, and response to therapy. Treatment of IRC aiming to prevent organ failure and improve symptoms includes remission induction with highly effective glucocorticosteroids and long-term maintenance of remission with immunomodulators such as glucocorticosteroid sparing additives or B cell depleting approaches.
Keywords: autoimmune pancreatitis; biliary bicarbonate umbrella; cholangiocarcinoma; IgG4-related disease; primary sclerosing cholangitis